ダイ20ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1979-1980 - 山崎, 道夫; ヤマザキ, ミチオ; Yamazaki, Michio (1981)
P(論文) 第20次越冬隊30名は, 1979年2月1日から1年間, 気水圏部門の「南極域気水圏観測」(POLEX-South)と地学部門の「鉱物資源に関する基礎調査, 第I期計画」を重点とする各種の観測・調査活動を行った。前者は, みずほ基地を中心に展開され, 南極大陸中部高原カタバティック地帯における熱収支等について興味ある結果を得たほか, みずほ基地の奥100kmに無人観測点M2(A3)を設け気象観測等を行った。後者は, 10月以降のやまと・ベルジカ山脈地域における地質調査, 隕石探査に主眼がおかれ, 約3000個にのぼる隕石を採集した。昭和基地では, 例年どおり極光, 地磁気, 電離層, 気象, 地震, 潮汐などの定常観測のほか, 超高層部門の科学衛星信号の受信, 電波雑音, 極域じょう乱に関する各種観測, 環境科学部門のCO_2,NOxモニタリング, 医学の研究などが通年実施された。沿岸露岸地域の地学的調査も活発に行われた。 From February 1,1979 to January 31,1980,thirty men of the wintering party of the 20th Japanese Antarctic Research Expedition executed the observation and examination in many scientific projects, particularly laying emphasis on "Polar Experiment-South (POLEX-South)" as one of the subprograms of the Global Atmospheric Research Program (GARP) and on the geological survey as the first year of "Analysis of crustal structure of Antarctica". The former project was carried out around Mizuho Station, and at an unmanned meteorological station "Y 100" which was established at 71.3°S and 46.3°E (2600m above sea level), and much results were obtained about the heat budget in the inland highland (katabatic zone) of the Antarctic Continent. As for the latter project, long term geological survey and search for meteorites around the Yamato and Belgica Mountains were made from October to January. About 3000 pieces of meteorites were found and collected. At Syowa Station, in addition to the routine observation of aurora, geomagnetism, ionosphere, meteorology, seismology and ocean tide, reception of data signals from scientific observation satellites and observation of ionospheric disturbance in the polar region by the upper atmosphere section, monitoring of minor constituents such as CO_2 and NOx and sampling of rocks by the environmental science section, and research in medical science were performed throughout the year. departmental bulletin paper